2019
DOI: 10.1520/acem20180040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Central Opening in Masonry Infill on Lateral Behavior of Intermediate RC Frames

Abstract: Despite not being taken into account in structural modeling, the complex behavior of masonry affects the seismic performance of structures. The main aim of this study is to evaluate the effects of infilled frames with different percentages of openings on reinforced concrete (RC) moment frames. Initially, an experimental model was constructed and subjected to loading. Afterwards, corresponding numerical analyses were carried out based on the experimental model. A simplified micromodeling method with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
8
5
0
Order By: Relevance
“…According to the current study, the base‐shear of the infilled frame with 8% central opening is about 0.7–0.8 times that of the base‐shear of the solid infilled frame, which corresponds to a decrease of the base‐shear equal to 20%‐30%, at a corresponding lateral displacement ranging from 0.5 to 20 mm (Figure 7A). This decrease is almost the same with that resulted from the study conducted by Tekeli and Aydin 72 and Ahani et al 74 . as shown in Figure 7A (comparing the dashed‐blue and the dashed‐green curve with the solid‐red curve).…”
Section: Parametric Studysupporting
confidence: 89%
See 2 more Smart Citations
“…According to the current study, the base‐shear of the infilled frame with 8% central opening is about 0.7–0.8 times that of the base‐shear of the solid infilled frame, which corresponds to a decrease of the base‐shear equal to 20%‐30%, at a corresponding lateral displacement ranging from 0.5 to 20 mm (Figure 7A). This decrease is almost the same with that resulted from the study conducted by Tekeli and Aydin 72 and Ahani et al 74 . as shown in Figure 7A (comparing the dashed‐blue and the dashed‐green curve with the solid‐red curve).…”
Section: Parametric Studysupporting
confidence: 89%
“…as shown in Figure 7A (comparing the dashed‐blue and the dashed‐green curve with the solid‐red curve). From Figure 7D it is observed that, according to the current study the base‐shear of an infilled frame with central opening equal to 20% is about 0.5–0.7 times that of the solid infilled frame after the 0.5 mm lateral displacement, which is almost the same ratio with that resulted from the study conducted by Ahani et al 74 . (comparing the dashed‐green curve with the solid‐red curve).…”
Section: Parametric Studysupporting
confidence: 84%
See 1 more Smart Citation
“…There are numerous valuable historical buildings with complex architecture that impose researchers to replace the priceless experimental investigations by numerical modeling and assessing their behavior during the earthquakes (Milani et al, 2017;Valente et al, 2017). According to the outcomes of many studies (Sandoval and Roca, 2012;Ahani et al, 2019), the finite element method (FEM) is the most accurate and widely used tool for analyzing masonry structures, which are also used in numerical simulations of this research. In the current study, The Concrete Damaged Plasticity criterion, a modified form of the Drucker-Prager criterion, is used for numerical simulation (Kmiecik and Kaminski, 2011).…”
Section: -Numerical Studiesmentioning
confidence: 99%
“…The complicated geometric shape of many historical buildings constrains the modeling procedure even in FEM software in which the meshing is affected by numerous parameters, including convergence and unity problems. To solve this issue, new methods of modeling named simpli ed micro modeling and macro modeling with more simple geometry are used by the researchers (Betti and Galano, 2012; Vicente et al, 2018;Ahani et al, 2019). Predicting the behavioral content of masonries due to diversity of the used materials and load-displacement indices confronted with sensible errors.…”
Section: Introductionmentioning
confidence: 99%